INFORMATION NEEDS AND INFORMATION SEEKING BEHAVIOUR OF THE USERS OF LIBRARIES PARTICIPATING IN THE AGRINET - GAMMANPILA, S. L. (DEGREE OF MASTER IN LIBRARY AND INFORMATION SCIENCE, 1999)
A survey was c a r r i e d out to i n f o r m a t i o n seeking behaviour p a r t i c i p a t i n g in the AGRINET. s t r u c t u r e d and open-ended quest instrument. a s c e r t a i n i n f o r m a t i o n needs and of the users of l i b r a r i es A mailed questionnaire with ions was used as the research The r e s u l t s revealed that the a g r i c u l t u r a l s c i e n t i s t s i n S r i Lanka were a c t i v e l y engaged i n research work. T e a c h i n g / t r a i n i n g, management/administration, and extension were the other main f u n c t i o n s that they performed. T h e i r primary areas of research i n t e r e s t s were centered around t h e i r f i e l d s of subject s p e c i a l i z a t i o n . Plant p r o t e c t i o n , plant breeding and plant s c i e n c e s were t h e i r main subject s p e c i a l i z a t i o n. The main purposes of seeking information by a g r i c u l t u r al s c i e n t i s t s were to support research work i n progress and to keep pace with the l a t e s t developments i n t h e i r f i e l d s of i n t e r e s t s. About 32.3% of the a g r i c u l t u r a l s c i e n t i s t s d i d t h e i r l i t e r a t u re searches by themselves, while others obtained the a s s i s t a n c e of s e c r e t a r i e s , research a s s i s t a n t s , and l i b r a r i a n s.